Preliminary design of an actuation system for a morphing winglet - Dimino, Ignazio; Amendola, Gianluca; Di Giampaolo, Barbara; Iannaccone, Giuseppe; Lerro, Angelo (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
Morphing winglets are relatively new devices currently being investigated for a variety of aircraft from civil to military. By ensuring significant fuel saving and aerodynamic efficiency benefits, especially in aircraft offdesign conditions, morphing winglet may contribute to optimize aircraft lift distribution throughout the flight mission while providing augmented roll and yaw control capability. In the framework of Clean Sky 2 Airgreen 2 GRA ITD project, this paper deals with the preliminary design of a electromechanical actuation chain including both the motor, the linear actuator and the mechanical system suitable for a morphing winglet. Given a morphing winglet layout, not addressed in this work, the capability of the structure to enable morphing through smooth rigid-body kinematic of the embedded mechanisms was assessed through numerical simulations. An electro-mechanical Matlab/Simulink model of the actuation architecture was developed and used as a design tool to preliminary evaluate the complete system performance and the ability to cope with the expected morphing aeroshapes. Numerical analyses are given and compared with analytical calculations involving the actuation forces, shaft rotations and linear actuator strokes of the morphing winglet actuation system for a given design case and loads.